#TITLE_ALTERNATIVE# - ANDRIA (NIM 13603012), NOVI
Fighter aircraft is designed to be able to operate in some pre-determined conditions. It is so possible that the aircraft is operated in extreme conditions such as high speed and maneuver load. Therefore, tests to estimate possible failures that can happen in such extreme conditions are necessary. One phenomenon that can cause catastrophic failure and frequently happen to aircraft is flutter. Flutter speed is a critical speed at which aircraft structure oscillated with increasing amplitude. This report describes the flutter analysis of F-16 that carries a missile on each wing for anti-symmetric configuration. Flutter is analyzed for different varied parameters. This analysis is carried out to study the characteristics of flutter in a number of F-16 possible flight conditions to obtain the most critical configuration. The parameters to be analyzed are missile position along spanwise and chordwise, wing fuel reducing scenario, Mach number, and flight level. Dynamic structure system and flutter stability are analyzed using finite element method with the assistance of MSC. Nastran.